Automation and the Trade Unions, TUC pamphlet, 1956 (1956)
1956 1945-1960 "Automation and the Trade Unions, TUC pamphlet, 1956" [T0354.jpg], 1956, Trades Union Congress From the 1955 Congress onwards, the TUC became increasingly concerned about the impact of automation and technological innovation on employment and working methods. This report looks at the use of automated systems in production and the introduction of computers, such as the Lyons Electronic Office (LEO), which had replaced 27 clerks.